The study of refusals and pragmatic modifiers in jordanian arabic - Al Kayed, Murad; Al-zu’bi, Mohammad Akram; Alkayid, Majd (Acta Scientiarum. Language and Culture, 2020)
This study aims at investigating politeness strategies and pragmatic modifiers used by native speakers of Jordanian Arabic to perform the speech act of refusal. The data were collected from 24 hours of recorded conversations taken from different mixed and same-sex conversations by native speakers of Jordanian Arabic. The researchers observed these conversations and utterances that perform the speech act of refusal. The strategies of refusals were analyzed following Beebe, Takahashi, and Uliss-Weltz (1990) model, while pragmatic modifiers were analyzed following House and Kasper (1981) and Blum-Kulka, House, and Kasper (1989). The results of the study showed that the Jordanians used complex strategy more than direct and indirect strategies. The findings showed that Jordanians used many pragmatic modifiers to soften their refusals. The study found that external modifiers were more frequent than other types of pragmatic modifiers. The study also found out that culture affected the use of refusal strategies and pragmatic modifiers. The impact of culture appeared clearly in the fact that Jordanians tended to use Islamic religious expressions to mitigate their utterances. Besides, it seemed that Jordanians preferred complex strategies because they viewed repetition and using more than one strategy as a polite way to save the face of others.